2018
DOI: 10.1051/matecconf/201822501012
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Water-in-Biodiesel Emulsion Characteristics Produced by Ultrasonic Homogenizer

Abstract: Limited studies had been conducted using water-in-diesel emulsion produced from ultrasonic homogenizing method. In this study, Water-in-Biodiesel Emulsions (WiBE) produced using ultrasonic homogenizer were characterized and studied for their physical and chemical properties through various laboratory investigations. The data were then compared with WiBE produced using mechanical homogeniser by the current researchers. Physical characterization tests were carried out on 24 WiBE emulsions produced using an ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…HLB is a measure of the balance of the size and strength of the hydrophilic (water-loving) and lipophilic (oil-loving) groups of the surfactant [18]. An HLB of between four and six is the suggested range for the creation of stable W/O emulsions, and it has been suggested that a value outside of this range may not result in an emulsion of this type [13,19]. However, in publications by Mondal and Mandal [6] and Karim, et al [13], W/O emulsions were formed by using surfactants with HLB values of seven, eight and nine.…”
Section: Surfactants and Hlb Valuesmentioning
confidence: 99%
See 4 more Smart Citations
“…HLB is a measure of the balance of the size and strength of the hydrophilic (water-loving) and lipophilic (oil-loving) groups of the surfactant [18]. An HLB of between four and six is the suggested range for the creation of stable W/O emulsions, and it has been suggested that a value outside of this range may not result in an emulsion of this type [13,19]. However, in publications by Mondal and Mandal [6] and Karim, et al [13], W/O emulsions were formed by using surfactants with HLB values of seven, eight and nine.…”
Section: Surfactants and Hlb Valuesmentioning
confidence: 99%
“…An HLB of between four and six is the suggested range for the creation of stable W/O emulsions, and it has been suggested that a value outside of this range may not result in an emulsion of this type [13,19]. However, in publications by Mondal and Mandal [6] and Karim, et al [13], W/O emulsions were formed by using surfactants with HLB values of seven, eight and nine. The discrepancy here could relate to the fact that different oils have been used by researchers when making their emulsions, which may have altered the optimum HLB for their specific system.…”
Section: Surfactants and Hlb Valuesmentioning
confidence: 99%
See 3 more Smart Citations